UNIVERSITY TEACHER TRAINING IN TEACHING SKILLS (2012)
The research summarizes the contributions of research projects aimed at training, professional development and knowledge of the most valuable skills mastered by the faculty. We build a map of the teaching competencies most valued by experts, a large sample of teachers and tutors, at the end of the cycle, from which a model is designed to promote teacher training college and the consolidation of professional identity, or through the integration of quantitative and qualitative methods. It highlights two major forms of competence: domain linked to the keys of the EHEA, the society of knowledge, communication, research and innovation in teaching and those linked to improving the teaching process: professional identity, mentoring, planning, methodological system, media design, evaluation, they have to integrate teaching theory and practice in educational institutions.